EFEKTIFITAS PELAKSANAAN KEBIJAKAN ELECTRONIC-KARTU TANDA PENDUDUK (E-KTP) DI KECAMATAN TAMPAN BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKAN - Jusmar '; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The dynamics of the problems that arise regarding the application of e-ID card first so many problems there are indications in the provision of e-ID card project Such corruption, the second problem is the fact that quite interesting that the refusal by some private banks in Indonesia with the reason the E-ID card KTP is not the same as the previous, the third problem is: Based on the mandate of Article 63 Paragraph (3) of Law No. 23 Year 2006 concerning Population Administration Electronic Identity Card (e-ID) applies nationally, but in the case praktenya tersbut difficult to embodied, while the fourth issue is the implementation of e-ID card lifetime. Of the four issues above authors writing thesis proposal is focused on the problems that all third and fourth course this has a correlation with the author angkat.Ini title that attracts writers to lift the title: